METODĂ INTERACTIVĂ IN EDUCAŢIA ECOLOGICĂ A ELEVILOR (PANGEEA, 2025)
The environmental education for the modern school is a primary necessity, because very serious problems caused by global pollution. Case study method is well suited to environmental education that is integrated into the geography curriculum. The active training method which examines a case, a particular situation, authentic or hypothetical or simulated modeled to exist or may arise in a natural, social or economic. This method can be applied in the secondary school level to the environmental education. For example I chose the theme: "The Amazon Rainforest - Myths and Realities".